The social nature and outcome of the interactions in a non-monetary centred sharing economy: from a social exchange theory perspective - Radaelli, Stephano (University of the Witwatersrand, Johannesburg, 2021)
The sharing economy is a collective name for emerging platforms that are bringing strangers together and changing the landscape of consumption. Individuals have been using these sharing economy platforms as an alternative to traditional trade to exchange resources. This study refined to the context of a non-monetary form of the sharing economy, namely Couchsurfing, where the reliance on social relationships were expected to be more prevalent. The social relationships between peers during an exchange offered an opportunity to find applicability and relevancy for social exchange theory. This study aimed to clarify the social nature of the interaction in Couchsurfing and determine the outcomes from these Couchsurfing interactions. Using a phenomenological research design, 19 in-depth semi-structured interviews were conducted together with an immersive experience as an active participant of the chosen sharing economy platform, Couchsurfing. Couchsurfing is a sharing economy platform that enables travellers to stay with other members for free. The positionality of the researcher was from an insider perspective studying other insiders. The data collected was analysed using a thematic analysis approach. Social exchange theory was supported in finding that the social nature of the interaction in Couchsurfing was reciprocal. The reciprocal exchange was clarified as co-created, continuous and dynamic. Individuals revealed that there was a necessity for a reciprocal response directly from the recipient. The findings confirmed that Couchsurfers had unspoken and explicitly stated expectations of a reciprocal relationship which impacted the continuity of the exchange after the Couchsurfing experience. This study also identified different social benefits that individuals gained from their Couchsurfing interactions. Throughout, these 2 research findings espoused and expanded on previous contributions to the theoretical framework. The presence of generosity during the reciprocal exchange has challenged the theoretical premise that individuals wanted to maximise their gains. Further research into generosity during the reciprocal exchange has been recommended.
A thesis submitted in fulfilment of the requirements for the Doctor of Philosophy to the Faculty of Humanities, School of Human and Community Development, University of the Witwatersrand, 2021
Keywords: Sharing economy; Social exchange; Social exchange theory; Hospitality; Couchsurfing; Reciprocal; Reciprocity; Reciprocal exchange; Social interactions; Benefits of the exchange; UCTD